Projective synchronization of chaotic systems via backstepping design - Tarai (Poria), Anindita; Khan, Mohammad Ali (Zielona Góra: Uniwersytet Zielonogórski)
Chaos synchronization of discrete dynamical systems is investigated. An algorithm is proposed for projective synchronization of chaotic 2D Duffing map and chaotic Tinkerbell map. The control law was derived from the Lyapunov stability theory. Numerical simulation results are presented to verify the effectiveness of the proposed algorithm.
Keywords: Lyapunov function; projective synchronization; backstepping; design